CURRICULUM DEVELOPMENT MANAGEMENT ISLAMIC BOARDING SCHOOL IN COUNTERING RADICALISM - Ideal Patrah (Darul Ilmi Bina Insan Foundation, 2025)
This study aims to examine the management of Islamic boarding school curriculum development in countering radicalism, with case studies at Permata Nusantara Madani Islamic Boarding School (Kerinci Regency) and Syekh Daud al-Masrur Islamic Boarding School (Bungo Regency), Jambi Province. The method used in this research was a qualitative approach with a case study design. Data collection techniques were conducted through observation, in-depth interviews with kiai (Islamic scholars), teachers, and students, and documentation studies. The results show that both Islamic boarding schools actively develop a curriculum that emphasizes moderate, tolerant, and patriotic Islamic values. Learning materials are not limited to the yellow books but also include strengthening character education, national insight, and religious moderation. Curriculum development management is carried out in a participatory manner by the pesantren leaders (kiai), teachers, and administrators, taking into account the social context of the surrounding community.